Modified STAP conditions facilitate bivalent fate decision between pluripotency and apoptosis in Jurkat T-lymphocytes - Kim, Jee Young; Cheng, Xinlai; Alborzinia, Hamed; Wölfl, Stefan (Biochemical and biophysical research communications, 2016)
Low extracellular pH (pHe) is not only the result of cancer metabolism, but a factor of anti-cancer drug efficacy and cancer immunity. In this study, the consequences of acidic stress were evaluated by applying STAP protocol on Jurkat T-lymphocytes (2.0 × 106 cells/ml, 25 min in 37 °C). We detected apoptotic process exclusively in pH 3.3 treated cells within 8 h with western blotting (WB). This programmed cell death led to significant drop of cell viability in 72 h measured by MTT assay resulting PI positive population on flow cytometry (FCM) at day 7. Quantified RT-PCR (qRT-PCR) data indicated that all of above mentioned responses are irrelevant to expression of OCT4 gene variants. Interestingly enough, pluripotent cells represented by positive alkaline phosphatase (AP) staining survived acidic stress and consequently proportion of AP positive cells was significantly increased after pH 3.3 treatment (day 7). In general, acidic treatment led to an apoptotic condition for Jurkat T-lymphocytes, which occurred independent of OCT4 induction.
Gesehen am 13.05.2020